TATA KELOLA PERPUSTAKAAN SEKOLAH DI SMP NEGERI 1 DAN SMP NEGERI 2 MUARA PINANG - Ani Muliasari; Sudarwan Danim; Syaiful Anwar (UNIVERSITAS BENGKULU, 2018)
Abstract: This research is a descriptive research that aims to know the management of school library in Junior High School 1 and Junior High School 2 Muara Pinang Empat Lawang regency. This research use qualitative descriptive tecniques. The subject of this reseach are principal, library managers, teachers and students.The techniques of data collection were observation, interview and documentation. The result of this study indicate that management of library in Junior High School 1 and Junior High School 2 Muara Pinang has been implemented optimally following the national standar of the library although there are still some procedure that the implementation is still not fully followed.Keywords: management, school library, service